Pengaruh Flipped Classroom Berbasis Video Interaktif dan Simulasi terhadap Peningkatan Kemampuan Psikomotor dalam Pembelajaran Fiqih - Dwi Indah Vidia Fatma Indah Wati; Isnawati Nur Afifah Latif (Paedagogie, 2026)
This study aims to describe the implementation of the flipped classroom model based on interactive videos and simulations, determine the level of students' psychomotor abilities before and after the implementation of the model, and analyze its influence on students' psychomotor abilities in the Fiqh subject of grade VIII at MTs Sumbersari Kowang. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design, with a population of all grade VIII students totaling 44 students and a purposive sampling technique. Data collection was carried out through tests (pretest and posttest), questionnaires, observation, and documentation, while data analysis used descriptive statistics and hypothesis testing in the form of a t-test (independent sample t-test) with the help of SPSS. The results of the study showed that the implementation of the interactive video and simulation-based flipped classroom model worked well and received a positive response from students. Students' psychomotor skills in the experimental class significantly improved compared to the control class. This was demonstrated by the experimental class's average score of 88.59, a 27.41-point difference compared to the control class's 61.18. This was further supported by the t-test results with a significance value of 0.001 (<0.05), indicating a significant effect of the model's implementation. Therefore, it can be concluded that the interactive video and simulation-based flipped classroom model has proven effective in significantly improving students' psychomotor skills compared to conventional learning, making it suitable for use as an alternative, innovative learning strategy in Islamic jurisprudence (Fiqh).